Ayat Fabiayyi Alaa Iraabbikumaa Tukadzdzibaann Sebagai Inspirasi Kaligrafi Kontemporer (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
The purpose of making this final work is to visualize verses about being grateful for the blessings bestowed by Allah SWT, with the aim of direct preaching to oneself, appreciators and the general public. The method in making this work goes through several stages, namely: Preparation (observing and exploring), Elaboration (finding and gathering references), Synthesis (implementing main ideas/ideas), Concept Realization (creating works) and Completion Stage (in the form of reports and exhibitions of works end). In creating the work, the author uses acrylic paint and mixed media in the form of paper on canvas. The ten works that the author made each contain the theme of gratitude to Allah SWT, the resulting works measuring 100 x 120 cm with the title include: Al-Quran, Allah's Creatures, Sun and Moon, Plants, Sky without pillars , Earth where life is, The vast ocean, Balance of Justice, Pearl and Marjan, Every moment is busy.